OP0142-HPR Psychometric Characteristics of a Spanish Translation of the Manchester Foot Pain and Disability Index: Validation and Rasch Analysis. (23rd January 2014) - Gijon-Nogueron, G.; Ndosi, M.; Luque-Suarez, A.; Alcacer-Pitarch, B.; Munuera, P. V.; Adam, G.; Redmond, A.
Abstract : Background: The Manchester Foot Pain and Disability Index (MFPDI) is a self-assessment questionnaire developed in the UK to measure foot pain and disability in the general population 1 . It has been translated and validated in several languages 2, 3 Objectives: The aim of this study was to conduct cross-cultural adaptation and validation of the MFPDI into Spanish Methods: The cross-cultural adaptation process was undertaken using International Society for Pharmacoeconomics and Outcomes Research (ISPOR) 4 recommendations. This involved 8 stages: i) Forward translation, ii) Reconciliation, iii) Back translation, iv) Back translation review, v) Harmonisation, vi) Pilot, vii) Pilot review, and viii) Proofreading. In the validation phase, the MFPDI datasets from the UK (original) and Spain (adapted) were pooled and subjected to Rasch analysis. Fit to the Rasch model, unidimensionality, reliability and cross-cultural invariance is reported Results: The pooled dataset comprised 1015 patients (Spain n=333 and UK n=682) with characteristics summarised in Table 1 . Rasch analysis confirmed three subscales for both the Spanish and UK datasets and fit to the Rasch model X 2 (df) = 15.945 (12), p = 0.194 and 31.024 (21), p = 0.073, for Spain and UK. The reliability (Person Separation Index - PSI) was .85 and .82 for Spain and UK respectively. Significant cross-cultural non-invariance was present on the Functional and Personal appearance subscales. Adjustment for the bias was achieved by 'splitting' the affected subscales and creation of cultural-specific subscales for each country and cultural-general subscale. Fit to the Rasch model was satisfied following cross-cultural adjustment (Table 1 ). The MFPDI was calibrated into interval-level scales for Spain and UK to enable future data pooling or comparisons. Conclusions: A gold standard translation process (ISPOR) has been used to develop a Spanish (for Spain) version of the MFPDI, a widely used foot-specific patient-reported outcome measure. Rasch analysis has confirmed that the MFPDI is a robust 3-subscale measure of foot pain, function and appearance in both its English and Spanish versions. Future work can make cross-cultural comparisons using the calibrated scales References: Garrow AP et al. Development and validation of a questionnaire to assess disabling foot pain. Pain 2000;85(1):107-13 Kaoulla P et al. Development and validation of a Greek language version of the MFPDI. Health Qual Life Outcomes. 2008 Jun 1;6:39 Ferrari SC, et al. Índice Manchester de incapacidade associada ao pé doloroso no idoso. Rev Bras Reumatol.2008;48(6):335-41. Wild D, et al. Principles of Good Practice for the Translation and Cultural Adaptation Process for Patient-Reported Outcomes (PRO) Measures. 2005. Disclosure of Interest: None Declared